Inequality and growth in rural China: does higher inequality impede growth? - Dwayne Benjamin; Loren Brandt; John Giles (Institute for the Study of Labor (IZA), 2006)
We explore the relationship between the level of village inequality in 1986, and the subsequent growth of household incomes from 1986 to 1999. Using a detailed household-level data set from rural China, we find robust evidence that initial inequality is negatively related to subsequent household income growth. We are able to address a number of econometric issues that affect the use of aggregate data for this exercise, especially measurement error and aggregation: Our results strongly suggest that village inequality has an external adverse impact on household-level income trajectories. However, once we account for possibly fixed village-level unobserved heterogeneity, we find no evidence that changes in inequality are correlated with household income growth: Whatever factor drives the inequality-growth relationship only operates in the long run. We explore several possible avenues by which initial inequality or an unobserved variable correlated with it affects household income growth. While we do not find the precise mechanism, our findings point toward a class of explanations based on collective choice (like the provision of public goods or determination of local taxes), and away from credit-market based explanations.
urn:nbn:de:101:1-20090825156
Keywords: 330